2019
DOI: 10.15625/0866-7136/12835
|View full text |Cite
|
Sign up to set email alerts
|

Crack identification in multiple cracked beams made of functionally graded material by using stationary wavelet transform of mode shapes

Abstract: This paper presents crack identification in multiple cracked beams made of functionally graded material (FGM) by using stationary wavelet transform (SWT) of mode shapes and taking into account influence of Gaussian noise. Mode shapes are obtained from multiple cracked FGM beam element and spring model of cracks. The theoretical development was illustrated and validated by numerical examples. The investigated results show that crack identification method by using SWT of mode shapes is efficient and realizable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…node of curvature (where curvature vanishes) makes no effect on the mode shape, curvature including the approximate one. In general, Equations (22), (24) allow one to obtain…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…node of curvature (where curvature vanishes) makes no effect on the mode shape, curvature including the approximate one. In general, Equations (22), (24) allow one to obtain…”
Section: Discussionmentioning
confidence: 99%
“…Chandrashekhar and Ganguli [20] applied the fuzzy logic system that allows the curvature-based technique to detect small damage with noisy measured mode shape. The wavelet transform is a useful tool for revealing small localized change in a signal [21] and was employed for crack detection in beam structures using mode shape [22] and curvature [23]. However, it requires a large amount of input data and is strongly sensitive to noise or miscalculation of input data.…”
Section: Introductionmentioning
confidence: 99%
“…However, the solution satisfying additionally conditions Eq. (10) and acknowledged as general solution for free vibration in multiple cracked FGM beam can be represented as (Lien and Duc, 2019…”
Section: mentioning
confidence: 99%
“…Nazari and Abolbashari (2013) and Abolbashari et al (2014) showed that the artificial neural network provides an efficient technique for double and multiple crack identifications in FGM beams. Zhu et al (2019) proposed a procedure for crack identification in an FGM beam using continuous wavelet transform (CWT) and Lien and Duc (2019) investigated the problem of crack identification based on stationary wavelet transform (SWT) of mode shapes. Recently, Lien et al (2019a) proposed a method combining neuron network (NN) and SWT of mode shapes and dynamic deflections for crack identification in cracked multi-span FGM beams.…”
Section: Introductionmentioning
confidence: 99%